Association between DNA damage repair gene somatic mutations and immune‐related gene expression in ovarian cancer. (28th January 2020) - Tian, Wenjuan; Shan, Boer; Zhang, Yuzi; Ren, Yulan; Liang, Shanhui; Zhao, Jing; Zhao, Zhengyi; Wang, Guoqiang; Zhao, Xiaochen; Peng, Dongxian; Bi, Rui; Cai, Shangli; et al.
Abstract: Background: Defects in DNA damage repair (DDR) system may lead to genomic instability and manifest as increased immunogenicity. DDR deficiency is prevalent in ovarian cancer (OvCa); however, the association of DDR mutation with immune profiles in OvCa remains largely unknown. This knowledge will provide an essential basis to the rational design of biomarker‐guided immune combination therapy of OvCa in the future. Methods: Whole‐exome sequencing data of 587 OvCa from The Cancer Genome Atlas (TCGA) were used to determine the expression profiles of 47 immune‐related genes and the abundance of tumor‐infiltrating immune cells. A Chinese OvCa cohort (n = 220) tested by next‐generation sequencing (NGS) was used to validate the association between DDR status and tumor mutation burden (TMB). Results: A total of 19.3% in TCGA cohort and 25.9% in Chinese cohort harbored at least one DDR somatic mutation. DDR deficiency exhibited a distinct immune profile with significant higher expression levels of PTPRCAP, CCL5, IFI16, LAG3, IL15RA, and GBP1 in OvCa in the TCGA cohort. Different DDR pathway deficiency displayed various immune profiles. Increased levels of Th1 cells, TMB, and neoantigen were also observed in DDR‐deficient tumors. Conclusions: DDR deficiency was associated with specific immune signatures in OvCa. Our findings emphasize the urgent need for biomarker‐guided rational immune combination therapy to maximize the OvCa patients who could benefit from immunotherapy. Abstract : DDR deficiency exhibited distinct immune profiles in ovarian cancer. DDR deficiency was associated with higher levels of TMB, neoantigen, genomic instability, and improved prognosis in ovarian cancer.